Exploring the link between soil health and crop productivity - Yingying Xing; Xiukang Wang; Adnan Mustafa (Ecotoxicology and Environmental Safety)
Understanding the complex interactions of plants and soils in the face of global food security and environmental degradation challenges is critical to the future of sustainable agriculture. This review discusses the important link between soil health and crop productivity by providing and comprehensive assessment of soil properties and management methods. By examining the physical, chemical, and biological properties of soil, it uncovers the key limitations posed by the soil environment on crop growth. The review highlights how soil texture, nutrient availability, and moisture levels directly impact on root growth, water uptake, and nutrient use efficiencies, while also exploring how diverse cropping systems enhance soil ecology and biodiversity. By utilizing state-of-the-art bioinformatics, we offer an in-depth exploration of rhizosphere microbial communities, emphasizing the functions of phosphate-solubilizing and nitrogen-fixing bacteria in promoting vital nutrient cycles. The potential of using microbial fertilizers to increase crop resistance to disease and stress hold a major premise for future sustainability in agriculture. In this regard, this review highlights the long-term impacts of crop cultivation on soil microbial diversity, revealing intricate selection processes between crops and their microbial partners in shaping crop-soil-microbe interactions. In terms of soil management, practical nutrient management strategies are proposed based on soil testing, emphasizing the benefits of organic farming and conservation tillage for soil health. Modern precision agricultural tools and remote sensing technologies are encouraged to be refined for effective nutrient management. At the policy level, we evaluate international guidelines aimed at fostering agricultural sustainability, suggesting new research pathways for crop-soil dynamics and offering approaches for developing soil health indicators in the face of global environmental challenges.